The Influence of Audit Time Budget Pressure on Reduced Audit Quality Behavior - Manatap Berliana Lumban Gaol (Journal of Accounting Research, Organization and Economics, 2018)
Objective – The purpose of this study is to examine the effect of audit time budget pressure on audit quality reduction behavior conducted by auditors in Indonesia.Design/methodology – 240 respondents for current study where auditors in Indonesia served as the sample. Multivariate technique was deployed to data analysis using AMOS - structural equation modeling. Results – The results of this study indicate that the audit quality reduction behavior occurs  in the audit assignment practices and this is becoming a concern in audit profession. Research finding statistically highlighted that there is a positive and significant relationship between time budget pressure and audit quality reduction behavior. Keywords Audit Quality, Time budget pressure, Reduce Audit Quality Behavior